School-Aged Children in Vancouver, Canada Do Not Meet Dietary Choline Recommendations but Meet Recommendations for Folate and Vitamin B12. (7th June 2021) - Wiedeman, Alejandra; Dhillon, Amneet; Innis, Sheila; Elango, Rajavel; Devlin, Angela
Abstract: Objectives: Nutrients such as choline, betaine, folate, and vitamin B12 are required for proper growth and development, but little is known about these nutrients in children. Our objective was to determine intakes and biomarkers of these nutrients in school-aged children (5 to 6 years old). Methods: A cross-sectional study of healthy children (n = 285) recruited from Vancouver, Canada were assessed. Dietary information was collected using three 24-hour recalls. Nutrient intakes were estimated using the Canadian Nutrient File and USDA database for choline; supplement use was collected by questionnaire. Plasma biomarkers were quantified by mass spectrometry and immunoassay. Results: Daily dietary intakes were (mean ± SD) choline 250 ± 96 mg, betaine 88 ± 41 mg, folate 335 ± 126 µg DFE, and vitamin B12 3.78 ± 2.71 µg. Top food sources were dairy and eggs (42–57%) for choline and vitamin B12, and cereal and grains (41–60%) for betaine and folate. Only 40% of children met the choline adequate intake (AI) recommendation for North America (≥250 mg/d); 81.5% met the European AI (≥170 mg/d). Plasma free choline, betaine, and dimethylglycine concentrations were (mean ± SD) 8.62 ± 2.13 µmol/L, 45.3 ± 13.7 µmol/L, 3.34 ± 1.03 µmol/L, respectively. Dietary choline intake and plasma free choline were not related. However, dietary choline intake was positively associated with plasma dimethylglycine. Less than 5% of children had inadequate folate and vitamin B12 intakes. More than half of the children (59.4%) were consuming a supplement containing B-vitamins, but none included choline or betaine. Some children (5.26%) had total folic acid intakes above the North American upper limit (UL; >400 µg/d); 10.90% had intakes above the European UL (>300 µg/d). Vitamin B12 intake was positively associated with plasma total vitamin B12 (mean ± SD; 594 ± 158 pmol/L) in an adjusted model (sex, age, total energy intake, and supplement use; p < 0.05). Conclusions: Our findings suggest that many school-aged children are not meeting dietary choline recommendations. Some children may have excessive folic acid intakes. The impact of imbalanced methyl nutrient intakes during this active period of growth and development needs to be determined in the future. Funding Sources: CIHR, NSERC, and BC Children's Hospital Research Institute.